Management of Hemorrhage Related to Direct Action Oral Anticoagulant Medication: Manejo das Hemorragias Relacionadas aos Anticoagulantes Orais de Ação Direta - Ganem, Isabela Ramos Ali; Martins, Luiz Claudio Behrmann; Tomé, Carlos Eduardo Mendonça (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
Introduction: Direct Oral Anticoagulant – DOACs) are a new class of anticoagulant that directly inhibit the trombine (dabigatrane) or Xa factor (rivaroxabane, edoxabane and apixabane) in the coagulation cascade. These medications are being more frequently used for the treatment and prevention of thrombolytic events, mainly in patients with atrial fibrillation, in substitute to varfrine or other vitamin K antagonists (VKAs). Although the incidence of hemorrhage is higher in AVKs than in DOACs, these events may also occur in this group, even in the form of intracranial hemorrhage (ICH), with risk of death. Nowadays, DOACs indications have progressively enhanced and the availability of their specific reverse agents certainly will enhance the safety of their usage. Idarucizumab, reverse agent of dabigatrane, and alpha andexanet, reverse agent of Xa factor, have been approved by the Food and Drug Administration in the United States and ciraparantag may be approved in a near future. Objective: To review the literature on the manage of hemorrhage related to the use of DOACs. Methods: Review of literature that used articles from 1998 to 2017, from several platforms and journals. Conclusion: DOACs constitute a great advance in prophylaxis and treatment of thrombolytic diseases, which presents elevated morbid mortality, and hemorrhages are the main adverse events related to their usage, being rarely necessary the immediate reverse of the anticoagulation. However, the existence of DOACs specific reverse agents enhances the safety of patients, whose anticoagulation may be rapidly reversed if necessary.